Implementing Teaching Strategies to Foster Critical Thinking in EFL Comprehension Skills with 7th Grade Students (2017)
ABSTRACT: This paper presents the experience of an action-research project that implemented teaching strategies to foster critical thinking in terms of listening and reading among 7th grade students in a private school in Medellin. Class observations showed that students required going beyond the usual literal comprehension tasks in order to exploit their proficiency. Additionally, the school’s EFL assessment methodology required to find ways to teach and assess critical thinking for comprehension separately from production. In order to achieve this, the study implemented listening and reading interpretive exercises conceived through Bloom’s taxonomy and theoretical considerations on critical thinking. Findings showed that students learned habits and skills to think critically on reading and listening input through interpretive exercises.